The relationship between household good security and incidence of stunting in toddlers during the new normal: A systematic review - Dwi Syaputri Yanti; Sumardiyono Sumardiyono; Kusnandar Kusnandar (Epidemiology and Society Health Review (ESHR), 2023)
Background: Stunting is a growth disorder and malnutrition problem experienced by toddlers worldwide and affects the quality of human resources that have an essential role in developing a nation. Households experiencing food insecurity led to a lack of nutritional intake and stunting. This work aimed to analyze the relationship between household food security with the incidence of stunting in toddlers during the new normal era. Method: This was a systematic review design conducted by searching relevant articles from some databases: Google Scholar, PubMed, and Science Direct using the keywords (“Household Food Security” OR “Food Security Families”) AND (“Stunting” OR “Stunted” “Nutritional Status”) AND (“Toddlers” OR “Children”) AND (“New Normal” OR “Adaptation of “new habits”) in Bahasa Indonesia and English. This work was performed following PRISMA guidelines. Articles were selected based on inclusion criteria: publication date from 2017 to 2022, food security with stunting incidence and factors affecting stunting, full text, open access, and academic journals. Articles were analyzed using a matrix table. Results: Based on the search results for articles that match the keywords, there are 333 articles. Of these, ten articles come from Indonesia, Iran, and Rwanda. The analyzed articles were selected from 10 articles. Conclusion: This study concludes that there is a relationship between household food security and the incidence of stunting in toddlers during the new normal.